Relação entre eficiência e rentabilidade no setor bancário brasileiro - Rosa, Robson Machado da (2007)
This work presents a contribution to the study of the relationship between the efficiency and the profitability in the brazilian banks sector, acted by the 50 (fifty) larger banks that act at the country, classified, annually, by Brazil s Central Bank (BACEN), in the period from 2002 to 2005. The efficiency was determined through the data envelopment analysis (DEA), under the vision of the models CCR and BCC, being calculated four efficiency types: standard, inverted, composite and normalized. While the profitability was determined through the added economic value added (EVA®). The necessary data to the development of the study were extracted of the database supplied by BACEN. As analysis technique was used the lineal correlation, that has as function to determine the correlation coefficient (r) among the variables. The results show that don t exist relationship evidences between the efficiency and the profitability in the national banks sector.